Птица: [сборник рассказов] / Анна Аркатова - Аркатова Анна (Эксмо, 2021)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58742 / Цена: 620.66 / Сис.шифр: 84(2=411.2)6 / Авт.знак: А 82 / ГРНТИ: 17.82.32 / ББК: 84(2=411.2)6-44